Arranjos familiares importam? Filhos corresidentes e mercado de trabalho no Brasil - Solange de Cassia Inforzato de Souza; Magno Rogério Gomes; Maria Vitória Silva Cinto (Revista de Economia Mackenzie)
This article investigates the influence of family structure on the insertion and occupational absorption of cohabiting children in Brazil. Based on the Pnadc 2022 microdata and the application of logistic regression, the highest probabilities of participation and lower chances of employment of sons and daughters of single-parent families in the market are affirmed. Children of single-parent families suffer less interference from factors that promote participation, such as education, age, non-white skin color and residence in the center-south of the country, and from reducers, such as females. The female gender compromises employment, but the impact on single-parent families is smaller. Education is central to the employment of sons and daughters in single-parent families, but less decisive to market participation. Single parenthood mitigates gender inequalities in the decision to work and in the occupation of women in the market. These results can help the formulators of evidence-based public policy in Brazil.